2018
DOI: 10.1136/annrheumdis-2017-212149
|View full text |Cite
|
Sign up to set email alerts
|

Splicing variant of WDFY4 augments MDA5 signalling and the risk of clinically amyopathic dermatomyositis

Abstract: Objectives Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of rare autoimmune diseases in which both genetic and environmental factors play important roles. To identify genetic factors of IIM including polymyositis (PM), dermatomyositis (DM), and clinically amyopathic DM (CADM), we performed the first genome-wide association study (GWAS) for IIM in an Asian population.Methods We genotyped and tested 496,819 SNPs for association using 576 IIM patients and 6,270 control subjects. We also exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…in a Japanese population, no significant association signal ( P < 5 × 10 −8 ) within HLA region was found in any of total IIM, PM or DM patients compared to healthy controls . Instead, an intronic SNP of WDFY4 (rs7919656) was found to be significantly associated with clinically amyopathic DM . The lack of association to the HLA region in the Kochi study may be explained by the patient distribution in their study cohorts.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…in a Japanese population, no significant association signal ( P < 5 × 10 −8 ) within HLA region was found in any of total IIM, PM or DM patients compared to healthy controls . Instead, an intronic SNP of WDFY4 (rs7919656) was found to be significantly associated with clinically amyopathic DM . The lack of association to the HLA region in the Kochi study may be explained by the patient distribution in their study cohorts.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, despite that a number of studies confirmed HLA alleles as the strongest genetic risk factor in Western populations, in a recent IIM GWAS conducted by Kochi et al. in a Japanese population, no significant association signal ( P < 5 × 10 −8 ) within HLA region was found in any of total IIM, PM or DM patients compared to healthy controls . Instead, an intronic SNP of WDFY4 (rs7919656) was found to be significantly associated with clinically amyopathic DM .…”
Section: Discussionmentioning
confidence: 89%
“…Another example is the anti-melanoma differentiation-associated gene 5 (MDA5) autoAb that is used to diagnose progressive interstitial lung disease with poor prognosis among chronic fibrosing IIPs [17]. Although some reports support the hypothesis that such autoAbs are pathogenic [18,19], in the absence of direct proof, these autoAbs are thought to represent natural autoantibodies in chronic fibrosing IIPs.…”
Section: Chronic Fibrosing Idiopathic Interstitial Pneumoniasmentioning
confidence: 99%
“…Interestingly, it was later found to be under strong selection in the past 2000 years in the UK (Field et al, ). Several recent studies indicate the involvement of this gene in autophagy (Yuan et al, ), NF‐κB signaling (Kochi et al, ), and cross‐presentation in response to viral and tumor antigens (Theisen et al, ). This process highlights the significance of genetic studies in opening a window to understanding the functions of genes, although it may take years of functional characterizations.…”
Section: Functional Characterizations Of the Associated Genesmentioning
confidence: 99%